2019
DOI: 10.1021/acs.joc.9b02520
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)-Catalyzed Construction of Isocoumarins via Dual C–H/C–C Activation of Sulfoxonium Ylides

Abstract: A ruthenium(II)-catalyzed annulation between two molecules of sulfoxonium ylides is achieved, generating a variety of substituted isocoumarins in reasonable yields. This strategy features dual C−H/C−C activation in one pot and has a wide substrate scope and good functional group tolerance.I socoumarin and its derivatives are important natural lactones, which are generally found in natural products as a basic structure. 1 It was found that compounds with an isocoumarin structure have a certain physiological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Nearly at the same time, the same reaction was reported by Cheng and co‐workers under slightly different reaction conditions [51] . Huang et al .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nearly at the same time, the same reaction was reported by Cheng and co‐workers under slightly different reaction conditions [51] . Huang et al .…”
Section: Introductionsupporting
confidence: 77%
“…[50] Nearly at the same time, the same reaction was reported by Cheng and co-workers under slightly different reaction conditions. [51] Huang et al reported a Ru-catalyzed [5 + 1] annulation of 1-(2-aminophenyl)pyrroles with α-carbonyl sulfoxonium ylides for the synthesis of pyrrolo[1,2-a]quinoxaline derivatives (Scheme 47). [52] In 2021, Matsunaga et al described a Ru(II) and chiral carbonic acid catalyzed (4 + 2) annulation of sulfoxonium ylides with sulfoximines for synthesis of a chiral product via a carboxylate assisted mechanism where one enantioselective proton is selectively deprotonated by a chiral carboxylate base (Scheme 48).…”
Section: Rhodium-catalyzed Reactionsmentioning
confidence: 99%
“…In the course of developing transition metal-catalyzed deacylative cross-coupling of 1,3-diones with carbene precursors, we unexpectedly observed the α,α,α-trisubstituted ester products by using N,N -dimethylformamide (DMF) as solvent 49 52 . Herein we report a multicomponent synthesis of α,α,α-trisubstituted esters from 1,3-diones, diazoesters, and DMF using a rhodium(II) catalyst, in which one-oxygen, one-carbon (sp 3 ), and one carbon (sp 2 ), deriving from 1,3-diones, diazoesters, and DMF, respectively, are inserted into C(CO)−C bonds (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2012; Gao et al, 2015;Zhou et al, 2015;Chen et al, 2016;Wang et al, 2017Wang et al, , 2018Pan et al, 2018;Xie et al, 2018a;Xie H. et al, 2018), in the current report we present a combined experimental and theoretical study of ruthenium(II)-catalyzed homocoupling of α-carbonyl sulfoxonium ylides, affording a variety of isocoumarin derivatives under mild conditions (Scheme 1C). (Liang et al, 2018;Xu et al, 2018;Huang et al, 2019;Zhou et al, 2019;Wen et al, 2020;Zhu et al, 2020). DFT calculations (Shan et al, 2016(Shan et al, , 2018Yu et al, 2017;Lian et al, 2019;Ling et al, 2019) suggested that the reaction is realized by a formal [3+3] annulation initiated by Ru(II)-catalyzed C-H activation.…”
Section: Introductionmentioning
confidence: 99%